Clinical usefulness of mepolizumab in severe eosinophilic asthma - Menzella, Francesco (Ther Clin Risk Manag, 2016)
Asthma is a chronic inflammatory disorder of the airways with variable clinical severity from very mild and occasional symptoms to recurrent critical exacerbations, at risk of fatal or near-fatal outcome, in a small percentage of patients. Within the different inflammatory cascades involved in asthma, eosinophils play a central role in the pathogenesis and largely influence disease severity. Interleukin-5 (IL-5) is the main cytokine controlling eosinophil activity and proliferation at the site of inflammation. Mepolizumab was the first biological humanized anti-IL-5 monoclonal antibody tested in randomized clinical trials on eosinophilic asthma and other eosinophilic diseases. On the basis of several positive clinical efficacy data, it has recently been approved by the US Food and Drug Administration for the treatment of severe eosinophilic asthma. Unfortunately, high costs are at present a critical issue. Future studies will probably help in the correct selection of a potential “responder phenotype”, allowing the prescription of this promising therapy to appropriate patients and best define cost-effectiveness issues.